The failure mode study of the polymer ball interconnected IC package under board level thermal mechanical stress - Cheng-Chih Chen; Lee, Jeffrey; Lee, Dem; Lin, Alice (Proceedings of technical papers (International Microsystems, Packaging, Assembly, and Circuits Technology Conference. Print), 2016)
The polymer cored solder interconnect has been evaluated in board level strain concerned ball grid array type IC package for many years. The innovative ball design is developed to compensate the board level reliability weakness of current metal alloy interconnect such as mechanical and thermal fatigue endurance due to its unique spherical polymeric core able to absorb the strain energy generated during the service in field. In terms of large size BGA packages such as Ceramic BGA and FCBGA, which suffer more significant solder joint strain on the package corner, the polymer cored solder interconnect is adopted to be capable of withstanding solder joint deformation between PCB and package under board level stress due to its ductile characteristics. In the study, the daisy chained ceramic substrate based BGA with 29×29 mm sq. 483 IO, 1.27 mm pitch was surface mounted on OSP finished PCB with SAC305 NC solder paste, then subject to temperature cycling test until 3000 cycle at 0/100 degree C with 10min dwell. 2 types of solder ball, one is SAC305 and another is SnAg coated polymer core, were ball attached through standard package assembly process. After 3000 cycle, the electrical failure sample was taken for various failure mode observations through dye and pry analysis and cross section under OM and SEM, respectively. The typical failure mode across IC package was investigated for comparison between SAC305 and polymer cored solder and concluded polymer cored solder will outperform SAC305.